Kajian Literatur Kebutuhan Vitamin K pada Bayi dan Perannya dalam Pencegahan Perdarahan - Rahma Aprillia; Revalina Annisa Putri; Riestifa Tri Nastiawan; Shafa Salsabilla; Dwi Rukma Santi (Jurnal Riset Keperawatan dan Kesehatan, 2026)
Background: Vitamin K is a fat-soluble vitamin that plays a crucial role in blood coagulation in newborns. Newborns are at high risk of vitamin K deficiency due to limited placental transfer, low body stores, immature liver function, and low vitamin K concentrations in breast milk, which may lead to Vitamin K Deficiency Bleeding (VKDB). Objective: This study aimed to review the relationship between vitamin K deficiency and the risk of bleeding in newborns and to evaluate the effectiveness of vitamin K prophylaxis in preventing VKDB. Methods: A literature review with a qualitative descriptive approach was conducted by searching national and international articles published between 2022 and 2026 in the Google Scholar, PubMed, and ScienceDirect databases. Relevant articles were selected based on predetermined inclusion criteria and analyzed descriptively. Results: The review showed that vitamin K deficiency increases the risk of bleeding disorders in newborns, including cutaneous, gastrointestinal, and intracranial hemorrhage, which may result in severe morbidity and mortality. Premature infants and exclusively breastfed infants were identified as high-risk groups. Intramuscular vitamin K administration was consistently reported to be more effective than oral administration because it provides more sustained protection against VKDB. In addition, parental and healthcare providers' knowledge was identified as an important factor in improving adherence to vitamin K prophylaxis. Conclusion: Vitamin K prophylaxis, particularly through intramuscular administration immediately after birth, is an effective strategy for preventing VKDB. Strengthening education for parents and healthcare professionals is essential to improve awareness and reduce the incidence of vitamin K deficiency-related bleeding in newborns